Correlation of MTAP Immunohistochemistry With CDKN2A Status Assessed by Fluorescence In Situ Hybridization and Clinicopathological Features in CNS WHO Grade 2 and 3 Meningiomas: A Single Center Cohort Study. Issue 2 (13th December 2021) - Sasaki, Shoh; Takeda, Maiko; Hirose, Takanori; Fujii, Tomomi; Itami, Hiroe; Uchiyama, Tomoko; Morita, Kohei; Matsuda, Ryosuke; Yamada, Shuichi; Nakagawa, Ichiro; Ohbayashi, Chiho
Abstract: CDKN2A homozygous deletion has occasionally been reported in atypical and anaplastic meningiomas and is considered as one of the genetic alterations commonly involved in their recurrence and malignant progression. Methylthioadenosine phosphorylase (MTAP) immunohistochemistry is a promising surrogate marker for CDKN2A homozygous deletion in different cancers but has not been examined in meningiomas. We performed CDKN2A FISH and MTAP immunohistochemistry on specimens from 30 patients with CNS WHO grade 2 (n = 27) and 3 (n = 3) meningiomas, including specimens from primary and recurrent tumors and then determined whether MTAP immunohistochemistry correlated with CDKN2A homozygous deletion and clinicopathological features. CDKN2A homozygous deletion was detected in 12% (3/26) of CNS WHO grade 2 and 67% (2/3) of CNS WHO grade 3 meningiomas; 3 cases exhibited temporal and/or spatial heterogeneity. MTAP loss was in excellent concordance with CDKN2A homozygous deletion (sensitivity; 100%, specificity; 100%). MTAP loss/ CDKN2A homozygous deletion correlated with cellular proliferation (mitotic rate; p = 0.001, Ki-67 labeling index; p = 0.03) and poor prognosis (overall survival; p = 0.01, progression free survival; p < 0.001). Thus, MTAP immunostaining can be a surrogate marker for CDKN2A homozygous deletion in meningiomas, and MTAP loss/ CDKN2A homozygous deletion may be an important prognostic factor for meningiomas.